2011
DOI: 10.1590/s2179-975x2011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic invertebrate's distribution in a freshwater coastal lagoon of southern Brazil in relation to water and sediment characteristics

Abstract: Abstract:Aim: The objective of this study was to evaluate the influence of water and sediment characteristics on the abundance, richness and diversity of the benthic invertebrate community in Peri lagoon, a freshwater coastal lagoon located in central coast of Santa Catarina State; Methods: Samplings were performed in April, May and June 2009, in five different sites of Peri lagoon. The samples were taken with an EckmanBirge drag, totalizing 60 for the invertebrate community, and 45 for sediment. Water physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…Over the years, the lagoon showed a variation in water quality, which influenced the composition of the fish community and changed its diversity and dominance, although limnological variables did not differ among the sampled sites, reinforcing the idea suggested by Lisboa et al . () that the lagoon is a homogeneous environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, the lagoon showed a variation in water quality, which influenced the composition of the fish community and changed its diversity and dominance, although limnological variables did not differ among the sampled sites, reinforcing the idea suggested by Lisboa et al . () that the lagoon is a homogeneous environment.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the importance of this ecosystem, it is little studied. Of studies undertaken (Cardoso et al ., ; Hennemann & Petrucio, ; Lisboa et al ., ; J. S. Oliveira, unpubl. data; A. N. Penteado, unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that sediment deposition and decreased river depth are determinants of benthic community structure, being this factor more significant than water variables (Lisboa et al 2011). In the present study, the hydromorphological assessment was shown to be highly dependent on the presence of a riparian area, and the dense margin vegetation of the riparian zone prevented excess sediment deposition due to margin erosion (Tran et al 2010).…”
Section: Hydromorphological Assessmentmentioning
confidence: 99%
“…The low scores for the parameter sediment deposition observed in stretches #2, #3, #8, #9, #10, #11, and #12 (Fig. 3) were related to the formation of islands in the water body, which may affect the euphotic zone depths, resulting in a decrease in the diversity of benthic communities (Henry 2009;Lisboa et al 2011).…”
Section: Hydromorphological Assessmentmentioning
confidence: 99%
“…The regional climate is humid subtropical (Cfa, according to the Köppen climate classification), with stronger winds during the austral spring (September-November) (Fuentes et al 2013) and rainfall throughout the year, although more intense in the hottest periods (Hennemann and Petrucio 2011). The water intake system for supply purposes is configured for a mean flow of 0.2 m 3 s À1 (Lisboa et al 2011).…”
Section: Study Areamentioning
confidence: 99%